Statement of Memory pada Desain Furnitur sebagai Pleasure Ideology (Studi Kasus: Artes Living, Bandung) - Arianti Ayu Puspita (JURNAL RUPA, 2016)
Furniture has become one of the essential commodities in the country of Indonesia. It also influenced the design development on creative industries that currently appear. Uniqueness and originality of the visual aspect is an important factor in the design of furniture. Various creative methods become the hallmark or identity of the brand. Visual identity of furniture will be studied based on furniture as case study, from Artes Living as one of creative industries in Bandung. Pleasurable product used as main theoritical approach to find the visual identity. Visual narrative and ideology pleasure are the finding of the research, which become two main methods from Artes Living. The results of this research presented in qualitative approach to through design concept, design methods and visual character. It is expected that the design concept may become new ideas and provide inspiration and insight to young designers in the use of cultural elements in Indonesia.